Late Quaternary climate change shapes island biodiversity - Weigelt, Patrick; Steinbauer, Manuel Jonas; Cabral, Juliano Sarmento; Kreft, Holger (Nature (London), 2016)
Relatively rapid changes in island area, isolation and connectivity observed since the Last Glacial Maximum have had measurable effects on present-day biodiversity, with formerly larger and less well connected islands having a greater number of endemic species. Island diversity since the Last Glacial Maximum Our understanding of biodiversity on islands assumes that either they are the geologically static backgrounds for immigration and emigration, or that they are more dynamic, influenced by geological and tectonic change over millions of years. Neither model, however, accommodates the rapid change over the past 20,000 years or so, during which time the melting of ice caps has driven up sea levels by more than 100 metres, dividing up landmasses, making small islands smaller and more remote. Patrick Weigelt et al . find that such inundations have had a measurable effect on island plant biodiversity. In particular, islands that were larger during the Last Glacial Maximum have more endemic species today than one would expect from their current size and remoteness, whereas the number of native species is essentially the same. Island biogeographical models consider islands either as geologically static with biodiversity resulting from ecologically neutral immigration–extinction dynamics 1 , or as geologically dynamic with biodiversity resulting from immigration–speciation–extinction dynamics influenced by changes in island characteristics over millions of years 2 . Present climate and spatial arrangement of islands, however, are rather exceptional compared to most of the Late Quaternary, which is characterized by recurrent cooler and drier glacial periods. These climatic oscillations over short geological timescales strongly affected sea levels 3 , 4 and caused massive changes in island area, isolation and connectivity 5 , orders of magnitude faster than the geological processes of island formation, subsidence and erosion considered in island theory 2 , 6 . Consequences of these oscillations for present biodiversity remain unassessed 5 , 7 . Here we analyse the effects of present and Last Glacial Maximum (LGM) island area, isolation, elevation and climate on key components of angiosperm diversity on islands worldwide. We find that post-LGM changes in island characteristics, especially in area, have left a strong imprint on present diversity of endemic species. Specifically, the number and proportion of endemic species today is significantly higher on islands that were larger during the LGM. Native species richness, in turn, is mostly determined by present island characteristics. We conclude that an appreciation of Late Quaternary environmental change is essential to understand patterns of island endemism and its underlying evolutionary dynamics.